Maternal high-fat diet regulates glucose metabolism and pancreatic β cell phenotype in mouse offspring at weaning - Zheng, Jia (PeerJ, 2020)
BACKGROUND: Maternal malnutrition is a critical factor in determining the risk of obesity and glucose intolerance in offspring. However, little is known about the effects of a maternal high-fat diet (HFD) on the β cell phenotype in offspring, which is a major factor in glucose homeostasis, especially during the early life of offspring. METHODS: Dams were randomly fed a HFD (60% kcal from fat) or a chow diet before pregnancy and during gestation and lactation. Glucose metabolism and the β cell phenotype were assessed in male offspring at weaning. RESULTS: Dams fed a HFD showed impaired glucose tolerance. A HFD predisposed the offspring to increased impairment of metabolic health, including obesity, glucose intolerance and insulin resistance, compared with offspring from chow diet-fed dams. Furthermore, increased islet sizes and islet densities were observed in male offspring from HFD-fed dams at weaning. There were increases in the insulin-positive area, β cell mass and β cell proliferation in male offspring from HFD-fed dams at weaning age. Next, we further determined whether a maternal HFD could affect β cell apoptosis in mouse offspring and found that there was no significant change in β cell apoptosis between the HFD and control groups. CONCLUSION: Our study is novel in showing that a maternal HFD predisposes offspring to impaired glucose metabolism and has a profound effect on β cell mass and proliferation in offspring mice, which is observed in mice as early as at weaning age. However, further study to clarify the underlying mechanisms is warranted.